3D finite element investigation of the compressive membrane action effect in reinforced concrete flat slabs. (1st April 2017) - Genikomsou, Aikaterini S.; Polak, Maria Anna
Highlights: 3D nonlinear finite element models simulate the continuity of slabs. Membrane action results to higher punching shear load and smaller deflections. Crack pattern of continuous slabs is concentrated around the column. FEA of real floor system shows higher punching shear resistance compared to the isolated slab. Existing design codes seem to underestimate the punching shear capacity of actual slabs. Abstract: Design codes for punching shear resistance of flat slabs are based on test results obtained from isolated slab-column connections. However, by testing isolated slabs, the compressive membrane action of a continuous slab-column system is ignored. This can result in lower punching shear strength compared to the actual strength of the real slab system. Testing continuous slab system is very uneconomical and in most cases not possible. In this paper, finite element analyses (FEA) are performed in order to investigate the effect of the compressive membrane action in flat concrete slabs by comparing results from isolated specimens and continuous floor systems. The adopted FE formulation and the material parameters were previously calibrated on an isolated test specimen (SB1). At first, the calibrated FEA are used to investigate the boundary conditions of slab-column connection (SB1). Then, these boundary conditions are modified, and the slab is also considered to have larger in-plane dimensions in order to examine its continuity. Finally, numerical analyses of existing punching shear tests that examine the compressive membrane action effect are conducted to show the accuracy of the FEA model. All the numerical analyses indicate that the punching shear capacity of a continuous slab is higher compared to the capacity of a conventional isolated slab. The predictive capability of the FEA models can allow for future investigations on the effect of the compressive membrane action to supplement the limited testing background on this area, and to provide recommendations for future design provisions.